Cryptic genetic structure in an Argentinian population of Anastrepha fraterculus (Diptera: Tephritidae) evidenced by SSR markers and quantitative traits - Rodriguez, Angeles I. (2019)
In some regions of Argentina and Brazil, the South American fruit fly Anastrepha fraterculus (Wied.) (Diptera: Tephritidae) causes significant damage to crops. An efficient integrated management program requires knowledge of pest population dynamics, dispersion patterns, sexual and oviposition behaviour, and adaptive landscape. The present study combined simple sequence repeat (SSR) molecular markers and morphometric datasets in order to analyse the population structure and infer the oviposition resource use strategy of the females. Infested guava fruits were collected from nine wild trees in Tucumán, Argentina, and a total of 140 adult A. fraterculus were recovered. These were then measured for six morphometric traits and 89 of them were genotyped for eight SSR loci. Genetic variability estimates were high (expected heterozygosity = 0.71, allelic richness = 12.5), with 8 to 20 alleles per locus. According to Wright's F-statistics estimates, the highest proportion (83%) of genetic variation occurred within individuals while variance between and within fruits were similar (≈ 8.5%). Analysis of the cryptic genetic structure based on SSR using different approaches, namely discriminant analysis of principal components (DAPC) and sparse non-negative matrix factorization (SNMF), yielded results consistent with the occurrence of two clusters with virtually no admixture. Average kinship between individuals which had emerged from the same fruit (0.07) was lower than that expected for full-sib families. Univariate and multivariate analyses of phenotypic data showed 54-66% of variance among individuals within fruits and 34-46% among fruits. The comparison between phenotypic (PST) and molecular (FST) differentiation identified wing width and length as possible target of positive selection. The average kinship and high genetic variation within fruits, together with the highly significant genetic differentiation among fruits, supports the hypothesis that each fruit was colonised by about three ovipositing females. The results also indicate that females were able to disperse widely from the emergence site before mating and starting oviposition activity.